Environmental Assessment of Antang Landfill, Makassar, Indonesia, Based on Magnetic Susceptibility, Mineralogy, and Morphology Characterization of Magnetic Mineral Soil - Vistarani Arini Tiwow; Sulistiawaty Sulistiawaty; Yosie Andriani; Meytij Jeanne Rampe; Emma Julin Pongoh; Rymond Jusuf Rumampuk (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2025)
Waste from the Antang landfill is estimated to come from various sources, including industry, agriculture, and households. This waste often contains heavy metals and magnetic minerals that can accumulate in the soil, leading to increased magnetic susceptibility. This study aims to analyze the magnetic susceptibility, mineral composition, and morphology of magnetic minerals found in the Antang Makassar landfill. The research utilized several methods: the rock magnetic method for testing magnetic susceptibility, x-ray diffraction (XRD) for mineralogical analysis, and scanning electron microscopy with energy dispersive spectroscopy (SEM-EDS) for characterizing the morphology of magnetic minerals. The results indicated that magnetic susceptibility values ranged from 1.442 x 10-6 m³/kg to 33.523 x 10-6 m³/kg, suggesting the presence of ferrimagnetic minerals in the soil. The morphology of the magnetic minerals in the soil around the Antang Makassar landfill was characterized by various shapes, including nearly octahedral forms, spherules (or imperfect spheres), and angular shapes. The octahedral and angular forms are believed to result from pedogenic processes, while the spherules are associated with anthropogenic processes related to human activities.